Systematic Literature Review: Filsafat Ilmu dalam Konteks Administrasi Pendidikan - Dedy, Dedy (Journal of Innovation in Teaching and Instructional Media, 2024)
Philosophy of science can be a critical dialog partner for the development of science. This is because the philosophy of science is essentially a philosophical study of problems related to science. Educational administration as the entire process related to educational activities including directing, planning, coordinating, financing, reporting, to supervision in order to cover education. The purpose of this study is to collect and analyze various journals related to the philosophy of science in relation to educational administration. This research uses the Systematical Literature Review (SLR) method by identifying data sources one by one in accordance with the specified steps and procedures. The results of this study indicate that there is a link between the philosophy of science in the context of educational administration for maximum results if applied in educational institutions. By identifying trends, gaps and potential developments in this area, this research makes a significant contribution towards strengthening the philosophical basis of administrative decision-making. In addition, the findings of this research can serve as a foundation for academics, policymakers and practitioners to develop a more holistic, contextualized and relevant model of educational administration to the challenges of 21st century education.